Utilizing the Cooperative Integrated Reading and Composition (CIRC) Model for Enhancing Reading Comprehension in English as a Foreign Language (EFL) Learners - Tamara, Benedicta Cindy; Supian, Supian; Dallyono, Ruswan; Ladinata, Ladinata; Lebedeva, Alexandra Leonidovna (Makassar State University, 2024)
Abstract. Many students still struggle with reading comprehension, particularly in the areas of identifying topics, using proper grammar, understanding meaning, and expanding vocabulary. This study focuses on determining the effectiveness of applying the Cooperative Integrated Reading and Composition (CIRC) model in reading comprehension, especially in composing recount text. It focuses on finding solutions to the students' reading issues in relation to the four aspects including topic, grammar, meaning, and vocabulary. The pre-experimental research design was used to carry out this research. Pre-test observations in class were also carried out by researchers before implementing the CIRC model. After carrying out the pre-test, the CIRCL model continued to be applied in class. Random sampling was used with 30 students of VIII D Secondary School in Bandung. During the course of the investigation, classes were observed and reading assessments, including pre-tests and post-tests, were administered to students. The results of this research indicated that CIRC use both individually and in groups significantly helps students' reading comprehension abilities. It was shown that the students' active participation in the implementation of CIRC model enhanced their reading comprehension abilities. Students also demonstrated positive outcomes towards numerous activities and features of the CIRC model. This study suggests that the CIRC model can be integrated into teaching strategies in school to improve reading skills, and also encourages collaborative learning, which is essential for students’ social development in the classroom.Keywords: CIRC Model, reading comprehension, recount text